2021
DOI: 10.3390/biology10121296
|View full text |Cite
|
Sign up to set email alerts
|

Antibody and Protein Profiles in Glaucoma: Screening of Biomarkers and Identification of Signaling Pathways

Abstract: Glaucoma represents a group of chronic neurodegenerative diseases, constituting the second leading cause of blindness worldwide. To date, chronically elevated intraocular pressure has been identified as the main risk factor and the only treatable symptom. However, there is increasing evidence in the recent literature that IOP-independent molecular mechanisms also play an important role in the progression of the disease. In recent years, it has become increasingly clear that glaucoma has an autoimmune component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 207 publications
(251 reference statements)
0
3
0
Order By: Relevance
“…These results suggest that glial cell activation occurs during glaucoma. Muller cell bodies are located in the inner nuclear layer, and Muller cell processes form the inner and outer membrane [19]. The expression of glutamine synthetase (GS) in Muller cells of the ocular hypertension group decreased [20], especially in the ocular hypertension group caused by anterior chamber injection of atropine sulfate microspheres.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that glial cell activation occurs during glaucoma. Muller cell bodies are located in the inner nuclear layer, and Muller cell processes form the inner and outer membrane [19]. The expression of glutamine synthetase (GS) in Muller cells of the ocular hypertension group decreased [20], especially in the ocular hypertension group caused by anterior chamber injection of atropine sulfate microspheres.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated the involvement of the immune system in the pathogenesis of glaucoma. Increased autoantibody titers against ocular tissue antigens were observed in the sera and aqueous humor of normal-as well as high-pressure glaucoma patients [107][108][109][110]. Also, proteins of the immune system, including the complement proteins C1q, C3, and C8, were found to be upregulated in the aqueous humor of glaucoma patients.…”
Section: Contribution Of the Immune System In Glaucomamentioning
confidence: 97%
“…Не выявлено корреляционной взаимосвязи с уровнем внутриглазного давления, объемом и площадью нейроретинального пояска. Увеличение риска развития глаукомы установлено только у больных с высокими показателями TNFα, превышающими 165 пкг/ мл (OR=7,09, CI=1,61-3,27), p=0,004, что согласуется с ранее полученными результатами [3][4][5].…”
Section: Stavropol State Medical University Russian Federationunclassified